Islam Wasaṭiyah pada Masyarakat Desa Rejoagung Kabupaten Jombang (Perspektif Teori Tindakan Komunikasi Jurgen Habermas) - Safi'i, Imam (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
The presence of this paper tries to visualize the religious context of Wasatiah Islam which is practiced by a community on a small scale. Wasatch Islam is a group of people who present humanist-dialogical values, prioritize brotherhood over hostility, uphold harmony and tolerance between religious believers and avoid extreme paths. Related to this, as happened to the people of the village of Rejoagung, Jombang Regency. In this society, there are three religions (Islam, Christianity, and Hinduism) that live in harmony and harmony. Islam as the majority religion is the main driver in maintaining harmony between the two religions. Other people as a minority group have never experienced discrimination and domination. They are free to practice their beliefs and worship according to their respective religions. Seeing the reality of life like this, of course, is far different from reality in general, where conflicts often occur due to differences in SARA. So to answer the interest in the problem above, the theory used by the author in this paper is the communicative action theory from Jurgen Habermas which emphasizes the existence of communicative action patterns and deliberative attitudes in the public sphere. The results of this study indicate that Wasa'iyah's Islamic Attitude was built on three strengths. The first is the teachings attached to every religion adhered to by the people of the Rejoagung village, the second is the sacredness that is believed by every religious believer and the third is the spiritual power that is believed by every religious believer as a manifestation of the sanctity of religion. The birth of these three forces is based on the dialectic between the beliefs of the people of Rejoagung village and their predecessors as well as on the religious values ​​believed by them. Based on these three strengths, the people of Rejoagung village, especially Muslims, can create an Islamic attitude of wasatatiyah amid plurality.